2023
DOI: 10.1001/jamainternmed.2023.1554
|View full text |Cite
|
Sign up to set email alerts
|

Easily Neglected Manifestations in Electrocardiogram in the Prone Position

Abstract: This case report describes a patient in their 70s with chronic obstructive pulmonary disease and hypertension who presented with a 2-day history of cough, expectoration, and shortness of breath.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 11 publications
1
10
0
Order By: Relevance
“…In Florida, Republicans have controlled all branches of state government since 1999, but Democrats retained an overall edge in partisan registration until 2021. 5 The authors used distinct measures across states to operationalize political party affiliation, 1 which exacerbates the conflation of partisanship and ideology. For Ohio, they included individuals who voted in a party's primary election, suggesting ideological alignment with that party.…”
Section: Discrepancies In Estimating Excess Death By Political Party ...mentioning
confidence: 99%
See 2 more Smart Citations
“…In Florida, Republicans have controlled all branches of state government since 1999, but Democrats retained an overall edge in partisan registration until 2021. 5 The authors used distinct measures across states to operationalize political party affiliation, 1 which exacerbates the conflation of partisanship and ideology. For Ohio, they included individuals who voted in a party's primary election, suggesting ideological alignment with that party.…”
Section: Discrepancies In Estimating Excess Death By Political Party ...mentioning
confidence: 99%
“…Researchers must be cognizant of variation in how states report political party affiliation when attempting to extend this study's important results. 1 Patrick O'Mahen, PhD To the Editor Wallace et al 1 claim excess mortality among Republican-vs Democratic-affiliated voters. We see 5 limitations.…”
Section: Discrepancies In Estimating Excess Death By Political Party ...mentioning
confidence: 99%
See 1 more Smart Citation
“…To the Editor When patients are prone, it is common to perform an electrocardiogram (ECG) by placing the precordial electrodes on the patient’s back, which transposes the usual location of the precordial electrodes to the dorsum (anatomical mirror). The case reported by Zhang et al shows that a substantial anterior ST elevation can go unnoticed in the ECG recorded this way. In another article, based on a case series of 100 patients, Chieng et al demonstrated the limited diagnostic capacity of the ECG obtained in this way, and specifically, showed this method is “unreliable for the detection of anterior myocardial injury.”…”
mentioning
confidence: 99%
“…In Reply We would like to express our gratitude to Cobos Gil et al for their thought-provoking and insightful comments on our case report, which discussed how anterior leads ST-segment elevation might be missed on the findings of an electrocardiogram (ECG) recorded in the commonly used prone position. Their comments addressed a new prone ECG acquisition method based on the concept of the mirror image electrocardiogram reported by Kors and van Herpen .…”
mentioning
confidence: 99%